Fungal biocompounds as strategy to control infection associated with urinary catheter (Research, Society and Development, 2022)
Catheter-associated urinary tract infections continue to be of concern, given the growth of epidemiological data, costs, bacterial resistance, and complications and morbidity. Bioprospection of plants as a strategy to control pathogenic microorganisms has gained space in the literature, due to the wide diversity existing in the Brazilian flora, which allows the exploration of endophytic fungi and various compounds, to be used in planktonic cells or to inhibit the formation of biofilms. This review aims to address the formation of biofilm in bladder catheters and perspectives with endophytic fungi, secondary metabolites and bioactive compounds against pathogenic microorganisms. The present data demonstrate a favorable use of endophytic fungi in the control of gram-positive and gram-negative microorganisms. The metabolites extracted from endophytic fungi with antibacterial action can be categorized especially among the class of phenolic compounds. In addition, they can be used to control the formation of biofilms in medical devices, such as indwelling bladder catheters, which are very susceptible to microbial colonization, being responsible for severe and persistent infections.